Al-Biruni, Sultan Mahmud Al-Ghaznawi and Islamic universalism: the historical context - Zein, Ibrahim Mohamed (ISTAC, 2014)
By referring to certain politico-economic factors as a means to justify his work, this paper argues that al-Biruni's framing of his Tahqiq ma li al-Hind (AlBeruni's India) was a religious interpretation of the events surrounding Sultan Mahmud al-Ghaznawrs Somaneith campaign and does not bear in mind the broader canvas of Muslim-Hindu relations. This is argued by the fact that al-Birunrs the only sustained reference to Sultan Mahmud is the Tahqiq in reference to his decisions pertaining to the destruction, looting, and subsequent humiliation of the Somandth linga. Al-Bircinrs claim of Mahmild's destruction of Hindu economic prosperity, his heavy handed treatment of Hindus, and the profound Hindu hatred of Muslims all seem to be consequences resulting from the events that transpired on the Somanath campaign, as opposed to a more general appreciation of Muslim-Hindu relations. Moreover, the paper argues that al-Birunrs interpretation of these events in this manner must be understood in reference to the intended purpose of the Tahqiq, namely a treatise aimed at promoting meaningful and sophisticated Muslim-Hindu engagement based on a tacit acknowledgement and subtle propagation of Islam's universalistic assumptions. This interpretation of al-Biriini explains why he chose to ignore the many existing platforms upon which Muslims and Hindus appeared to have developed working relationships. This paper brings to light various Muslim-Hindu relationships to ensure al-Biruni is not misunderstood and that his framing of Mahmud should not be generalised to all forms of Muslim-Hindu engagement. Rather, al-Biruni was concerned with the meaningful advancement of Muslim-Hindu relations for which he chose to focus on representing Islam as a somewhat open religious and intellectual framework to appropriate various aspects of Hindu learning. It is in this manner that the universalism of Islam is emphasised